Production and reception of human resource management practices for health promotion - Storti, Beatriz Cintra; Sticca, Marina Greghi; Pérez-Nebra, Amalia Raquel (Frontiers in Psychology, 2023)
Organizations thrive when there is a healthy relationship between people, i.e., where there is high social capital. Human resource management practices (HRMP) contribute to promoting social capital and mental health in organizations. However, there remains a gap in the literature on practices to promote mental health, as well as on the difference in perception of the function of the practices between those who promote them and those who receive them. Thus, this study aimed to identify what HRMP oriented toward mental health promotions are, how they are perceived, and whether there is variation among these perceptions. Twenty managers and 11 subordinates were interviewed. To achieve the first two objectives, a content analysis was performed, and for the last, a lexical analysis. In the content analysis, the following categories emerged for both groups: work organization and idiosyncratic deals and affective social support. Only in the managers did the categories of informational support, communication, and maintaining good interpersonal relationships emerge. The lexical analysis suggested that managers perceive task-related practices as promoting mental health, while teams attribute importance to affective social support practices. HRMP psychological principles were described. Social support practices should be adopted as human resource protective strategies for mental health.